2020
DOI: 10.1177/2041669520911408
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Corridor Illusion in Pigeons: Humanlike Pictorial Cue Precedence Over Motion Parallax Cue in Size Perception

Abstract: Depth information is necessary for perceiving the real size of objects at varying visual distances. To investigate to what extent this size constancy present in another vertebrate class, we addressed the two questions using pigeons: (a) whether pigeons see a corridor illusion based on size constancy and (b) whether pigeons prioritize pictorial cues over motion parallax cues for size constancy, like humans. We trained pigeons to classify target sizes on a corridor. In addition, we presented a dynamic version of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
(84 reference statements)
2
4
1
Order By: Relevance
“…If the size constancy works perfectly, perceived sizes changed at the ratios of 65:75 and 85:75 for closer and farther conditions, respectively. These ratios correspond to the manipulation of pictorial cues in our previous study (115:135 and 155:135;Hataji et al, 2020). These ratios also correspond to the discrimination thresholds 65.7:73.9 and 73.9:84.9, which are calculated from the ratios of target size when the proportion of large key choices was 25% and 50%, and when it was 50% and 75%, respectively.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…If the size constancy works perfectly, perceived sizes changed at the ratios of 65:75 and 85:75 for closer and farther conditions, respectively. These ratios correspond to the manipulation of pictorial cues in our previous study (115:135 and 155:135;Hataji et al, 2020). These ratios also correspond to the discrimination thresholds 65.7:73.9 and 73.9:84.9, which are calculated from the ratios of target size when the proportion of large key choices was 25% and 50%, and when it was 50% and 75%, respectively.…”
Section: Discussionsupporting
confidence: 75%
“…This indicates that pigeons use motion parallax selectively for visuo-motor control and not for size constancy. We previously found that this species' visual size perception was not affected by motion parallax caused via relative object motion (Hataji et al, 2020). The difference between our previous study and this one is that motion parallax in the stimuli was object produced or selfgenerated.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations